Effectiveness of a Problem-Based Learning Model Integrated with Socio-Scientific Issues to Improve Science Process Skills of High School Students - Vegha Dwi Arthamena; Mizzan Ayubi; Sri Atun; Sarmila Eka Putri (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2025)
Problem-Based Learning (PBL) integrated with SSI (SSI-integrated PBL) is a learning model used to enhance science process skills based on the context of 21st-century skills. This study intends to investigate the difference in science process skills between students taught by using SSI-integrated Problem-Based Learning and those taught by using Problem-Based Learning on salt hydrolysis. Four classes (N = 136) at a high school in Mandau were the study participants. This study used two treatments: the experimental group using SSI-integrated Problem-Based Learning (PBL) and the control group using Discovery Learning (DL). Relevant data were collected using the science process skills instrument. The data were analyzed using ANOVA. The finding was confirmed for the PBL model with science process skills, with a significance value of < 0.05. Looking at the mean value, the average for students who take PBL differs from that of students who take DL. The PBL model in the experimental class can enhance science process skills better than in the control class. The study's findings were compiled via discussion of the literature review and recommendations process. The SSI-integrated PBL approach is significantly better than the DL model in enhancing science process skills. The percentage of the contribution of SSI-integrated PBL to science process skills is 8.9%, which shows a high influence.